Update on the ACTG1‐associated Baraitser–Winter cerebrofrontofacial syndrome. Issue 10 (30th May 2016) - Di Donato, Nataliya; Kuechler, Alma; Vergano, Samantha; Heinritz, Wolfram; Bodurtha, Joann; Merchant, Sabiha R.; Breningstall, Galen; Ladda, Roger; Sell, Susan; Altmüller, Janine; Bögershausen, Nina; Timms, Andrew E.; et al.
Abstract : Baraitser–Winter cerebrofrontofacial syndrome is caused by heterozygous missense mutations in one of the two ubiquitous cytoplasmic actin‐encoding genes ACTB and ACTG1 . Recently, we characterized the large cohort of 41 patients presenting with this condition. Our series contained 34 patients with mutations in ACTB and only nine with ACTG1 mutations. Here, we report on seven unrelated patients with six mutations in ACTG1 –four novel and two previously reported. Only one of seven patients was clinically diagnosed with this disorder and underwent ACTB/ACTG1 targeted sequencing, four patients were screened as a part of the large lissencephaly cohort and two were tested with exome sequencing. Retrospectively, facial features were compatible with the diagnosis but significantly milder than previously reported in four patients, and non‐specific in one. The pattern of malformations of cortical development was highly similar in four of six patients with available MRI images and encompassed frontal predominant pachygyria merging with the posterior predominant band heterotopia. Two remaining patients showed mild involvement consistent with bilaterally simplified gyration over the frontal lobes. Taken together, we expand the clinical spectrum of the ACTG1 ‐associated Baraitser–Winter cerebrofrontofacial syndrome demonstrating the mild end of the facial and brain manifestations. © 2016 Wiley Periodicals, Inc.